Thermal hydrolysis of poultry byproducts for the production of microbial media - Edward T. Drabold; Manish Sakhakarmy; Saravanan R. Shanmugam; Sushil Adhikari; Wellington Arthur; Marko Rudar; Melissa Boersma; Qichen Wang; Brendan T. Higgins (Scientific Reports)
Abstract Rendered meat byproducts are important feedstocks for pet food formulas, esterified biodiesels and other bioproducts. However, feedstocks with high water contents are currently not attractive for rendering due to the need to evaporate the resulting high protein “stick” water. Consequently, many wet meat byproducts, like poultry dissolved air flotation (DAF) solids, are land applied, wasting a potential resource, and causing malodor for nearby communities. Herein, we present a process for rendering wet meat byproducts where the stick water produced from rendering hydrolyzers is sold as value-added microbial media and therefore does not require evaporation. Thermal hydrolysis experiments were performed on a wet (7% solids content) and drier feedstock (25% solids). Amino acids, the most valuable component of microbial media, were marginally higher in stick water produced from the 25% solids feedstock (1.7 g/L) compared to the 7% feedstock (1.5 g/L) despite the much higher solids input. Furthermore, the fatty acid composition of the thermally treated solids was unchanged by reactor solids loading. Mass and energy balances were performed to understand the impact of feedstock solids concentration on heating requirements. This work uses a process engineering approach to develop a new paradigm in rendering technology: upcycling wet meat byproducts into value-added microbial media.